Manifestly Haraway - Haraway, Donna Jeanne (University of Minnesota Press, 2016)
"Electrifying, provocative, and controversial when first published thirty years ago, Donna Haraway's "Cyborg Manifesto" is even more relevant today, when the divisions that she so eloquently challenges–of human and machine but also of gender, class, race, ethnicity, sexuality, and location–are increasingly complex. The subsequent "Companion Species Manifesto," which further questions the human-nonhuman disjunction, is no less urgently needed in our time of environmental crisis and profound polarization. Manifestly Haraway brings together these momentous manifestos to expose the continuity and ramifying force of Haraway's thought, whose significance emerges with engaging immediacy in a sustained conversation between the author and her long-term friend and colleague Cary Wolfe. Reading cyborgs and companion species through and with each other, Haraway and Wolfe join in a wide-ranging exchange on the history and meaning of the manifestos in the context of biopolitics, feminism, Marxism, human-nonhuman relationships, making kin, literary tropes, material semiotics, the negative way of knowing, secular Catholicism, and more. The conversation ends by revealing the early stages of Haraway's "Chthulucene Manifesto," in tension with the teleologies of the doleful Anthropocene and the exterminationist Capitalocene. Deeply dedicated to a diverse and robust earthly flourishing, Manifestly Haraway promises to reignite needed discussion in and out of the academy about biologies, technologies, histories, and still possible futures."– Provided by publisher.
Keywords: LGBTQIA2+; animaux de compagnie; approches et analyses; chien; corps; cours; cyberféminisme; cyborg; discipline; discours dominant; identités LGBTQIA2+; lit4700; philosophie; point de vue situé; premier cycle; relations humains/animaux; ressource en ligne; sciences humaines; systèmes d'oppressions; technologie; thématiques

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (Rowman & Littlefield, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Section: xx, 236 pages
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques